O impacto da pandemia de Covid-19 na arrecadação própria e nos gastos com educação do Município de Fortaleza – CE: análises para o período 2018 a 2022 - Lopes Filho, José (2024)
This study analyzes the effects of the COVID-19 pandemic on tax collection in the city of Fortaleza. Between 2020 and 2022, the city had around 403,000 cases and almost 12,000 deaths resulting from the virus. To investigate the impacts, a descriptive analysis was carried out to observe the evolution of the variables and capture possible patterns of behavior and a comparative study, through a horizontal analysis, to better understand the evolution of finance and investigate a possible economic-financial trend. The descriptive analysis covers the years 2006 and 2022, while the horizontal analysis covers 2018 to 2022. In addition to Fortaleza, both analyzes were also carried out for Recife and Salvador as they are municipalities that have similar characteristics and financial perspectives. From the results, there are possible signs of a robust recovery in the capital's revenue in comparison with Recife and Salvador, as the capital of Ceará received the highest growth rates in tax revenues and taxes after the initial year of the pandemic in 2020. Furthermore, it was noted that Fortaleza played a leading role in education expenditure, even in 2020, the worst year of the pandemic in an economic sense.